Wear ratio and work surface finish during electrical discharge machining (EDM) with eccentric electrode - Khan, Ahsan Ali; Saad, Affendi; Mohd Isa, Mohd Zulfadli Isma (International Islamic University Malaysia, 2011)
Abstract. In the present work the performance of eccentric electrode during EDM has been studied. Material removal rate and tool wear rate increase with increase in spindle speed and feed rate. It was found that higher feed rate increases the wear ratio. Spindle speed values determined the flushing efficiency. A higher spindle speed improves the flushing efficiency and thus improves the surface roughness.